The Role of Behavioral Finance in Formal Debt Decisions Study of Micro Small Medium Enterprises (MSMEs) Semarang - Sri Suyati; Andalan Tri Ratnawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research is to examine behavioral finance and its effect on formal debt decisions to improve business performance in micro, small, and medium enterprises in Semarang. Many studies have been conducted related to behavioral finance, where overconfidence, the illusion of control, and availability will influence formal debt decisions. The characteristics of MSMEs in making debt decisions are strongly influenced by behavioral finance. The analytical method used is quantitative with Smart PLS. The results of the analysis of overconfidence have no significant effect on formal debt decision-making, the illusion of control and availability have a positive and significant effect on formal debt decisions, and formal debt decisions have a positive and significant effect on business performance.